Bahasa Komplain di Media Sosial Twitter - Ikke Dewi Pratama (TRANSFORMATIKA, 2017)
This research aims to know the speech function and politeness strategy used by speaker and interlocutor in dialogue which contains the complaint in twitter. It is descriptive qualitative research applied non-participant method. The source of data was the tweet dialogue about customer complaints or complaints between consumers and @indosat as producer in @indosat account. Purposive sampling technique was used to choose the data which represent the existence population. The analysis found that there are two functions of speaker’s utterance: complaining and responding. The politeness strategies used by speaker in complaining are bald on record, positive politeness, negative politeness, and off record. The politeness strategies used by speaker in responding are bald on record, positive politeness and negative politeness. Meanwhile, the function of utterance said by the interlocutor is giving response to the complaint by using positive and negative politeness strategy. It is hoped that the result of this research can be used as the reference for consumer and producer who interact in social media so that their resulting utterances do not emerge the conflict of both sides. Keywords: politeness, complaint, twitter, producer, consumer